2008
DOI: 10.1177/1523422307310103
|View full text |Cite
|
Sign up to set email alerts
|

A New Era for Career Development and HRD

Abstract: The problem and the solution. Career development (CD), long considered a primary function of HRD, has been eclipsed in recent years by changing employer-employee loyalties, increasing interest in portable careers, and the growing importance of subjective career goals. Instead of abandoning CD in the wake of such significant changes, HRD needs to review the evolving career landscape and respond to the diverse needs of individuals and systems. It is a new era for CD and HRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…With the evolution of contemporary careers from a sequence of occupations to a process that encompasses all work‐related activities that take place over the course of one's life (Hall, ), scholars have begun to conceptualize CD as an individual's unique process of growth (Hite & McDonald, ). More formally, Simonsen () has defined CD as ‘an ongoing process of planning and directed action toward personal work and life goals’ (quoted in Hite & McDonald, , p. 5).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…With the evolution of contemporary careers from a sequence of occupations to a process that encompasses all work‐related activities that take place over the course of one's life (Hall, ), scholars have begun to conceptualize CD as an individual's unique process of growth (Hite & McDonald, ). More formally, Simonsen () has defined CD as ‘an ongoing process of planning and directed action toward personal work and life goals’ (quoted in Hite & McDonald, , p. 5).…”
Section: Theorymentioning
confidence: 99%
“…With the evolution of contemporary careers from a sequence of occupations to a process that encompasses all work‐related activities that take place over the course of one's life (Hall, ), scholars have begun to conceptualize CD as an individual's unique process of growth (Hite & McDonald, ). More formally, Simonsen () has defined CD as ‘an ongoing process of planning and directed action toward personal work and life goals’ (quoted in Hite & McDonald, , p. 5). Newer theories and models have begun to support this shift to focus upon non‐traditional and non‐linear careers (Sullivan & Baruch, ), to offer alternative perspectives (Enache, Sallan, Simo, & Fernandez, ) that address some of the unique features of contemporary workers (Hall, ).…”
Section: Theorymentioning
confidence: 99%
“…It also enhances greater employee participation in organizational activities while improving their work skills. Thus, career development is one of the key drivers of employee development for the workplace of the future (Hite & McDonald, 2008). Career development programs have been identified as effectively increasing employment and developing adults' skills for remaining at or returning to organizations (Calo, 2008).…”
Section: Theoretical Framework Career Development For Older Workersmentioning
confidence: 99%
“…Hite and McDonald (2008) found that career development is an ongoing process of planning and directed action toward personal work and life goals. The result supports hypothesis 3 that career development (β = 0.77, p = 0.00) significantly affects academic staff's job satisfaction and is consistent with previous study, such as Ko (2012) revealed that there is significant correlation between job satisfaction and career development.…”
Section: Hypothesismentioning
confidence: 99%